First-line sintilimab plus chemotherapy in locally advanced or metastatic esophageal squamous cell carcinoma: A cost-effectiveness analysis from China - Shen, Jian; Du, Yi; Shao, Rong; Jiang, Rong (Frontiers in Pharmacology, 2022)
Objective: Aimed to assess the cost-effectiveness of sintilimab combined with cisplatin plus paclitaxel versus chemotherapy alone as first line treatment in patients with advanced or metastatic oesophageal squamous cell carcinoma from the Chinese healthcare system. Material and Method: A partitioned survival model was developed based on the ORIENT-15 clinical trial. Drug costs and health state utility were obtained from the literature. Outcomes included the health outcomes in life-years (LYs), quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER). One-way and probabilistic sensitivity analyses were performed to evaluate the model uncertainty Result: In overall population, patients in sintilimab plus chemotherapy gained more health benefit (0.90 QALYs VS. 0.61 QALYs) and cost more (15,399.21 US$ VS. 7475.58 US$) than patients in chemotherapy group. In subgroup, patients in sintilimab plus chemotherapy gained more health benefit (0.89 QALYs VS. 0.68 QALYs) and cost more (15,656.19 US$ VS. 9,162.77 US$) than patients in chemotherapy group. Compared with chemotherapy, patients receiving sintilimab plus chemotherapy had ICERs of $26,773.68/QALY in overall population and $30,065.50/QALY in subgroup, which was above the threshold of WTP. Conclusion: Sintilimab plus chemotherapy was more cost-effective than chemotherapy alone for patients with advanced esophageal cancer from the perspective Chinese healthcare system.